Analisis Penyebab Diesel Engine Low Power MTU 10V1600 Dengan Metode 7 Step Troubleshooting - Sukron Athoillah Rasyid; Rahmat Noval; Ahmad Bustomi (JOURNAL SAINS STUDENT RESEARCH, 2026)
The diesel engine MTU 10V1600 installed in the P01912 power car unit experienced a low power phenomenon that reduced its operational performance. This study aims to analyze the root cause of the failure using a descriptive qualitative method, with data collected through field observation, technician interviews, and literature study, integrated with the 7 Step Troubleshooting method, Root Cause Analysis (RCA), and a fishbone (Ishikawa) diagram based on the 5M categories (Man, Machine, Method, Material, Measurement). The investigation found that the main root cause of the low power was a failure in the air intake and exhaust system, consisting of massive deposits on the turbocharger compressor blades, total blockage of the intercooler passages, and a clogged air filter element, which collectively restricted the air supply to the combustion chamber and reduced engine speed from the standard 1,500 RPM (50 Hz) to 1,402 RPM (45.2 Hz). Corrective actions, namely turbocharger replacement and intercooler cleaning, successfully restored the engine output power to the manufacturer's standard specification of 400 kW (536 HP) at 1,500 RPM and 50 Hz, as confirmed by a running and performance test. This study recommends an update to the preventive maintenance Standard Operating Procedure (SOP), including daily dust indicator inspection, hour-meter-based air filter replacement, and periodic boost pressure monitoring, to prevent recurrence of similar failures in power car units in the future.